The Effect of Colored Sand Media on the Fine Motor Development of Children in Group B at TK YPPI Donggala - Nadia Nadia; Durrotunnisa Durrotunnisa; Fitriana Fitriana; Shofiyanti Nur Zuama (FKIP - Universitas Riau, 2026)
Understanding the development of children's fine motor skills through the use of colored sand media is crucial for teachers when providing stimuli to students. When learning with colored sand, children can enhance their imagination and exercise greater freedom in developing their physical fine motor skills. Utilizing colored sand media to develop fine motor skills in early childhood is a viable strategy, as it facilitates easier learning and practice for the children. The objective of this study was to determine the effect of colored sand media on children's fine motor development. This study employed a quantitative method with a descriptive experimental design. The subjects were 15 students from Group B at TK YPPI Donggala. Based on the results prior to the treatment, the data showed Very Well Developed (BSB) at 2.22%, Developed as Expected (BSH) at 11.11%, Starting to Develop (MB) at 55.56%, and Undeveloped (BB) at 31.11%. Conversely, the results after the treatment showed Very Well Developed (BSB) at 26.67%, Developed as Expected (BSH) at 53.33%, Starting to Develop (MB) at 20.00%, and Undeveloped (BB) at 0.00%. Data collection techniques included observation, interviews, and documentation. Data analysis was performed using percentage techniques and t-tests. The t-test results indicated a calculated t-value of 7.436 with a significance of 0.00. Since the significance value is less than 0.05, it is concluded that H0 is rejected and H1 is accepted. This indicates that the colored sand media method has a significant effect on the fine motor development of children in Group B at TK YPPI Donggala.